When the medium is not the message: Breivik, Tarrant, and the conceptions of history of contemporary right-wing extremist lone-actor terrorists - Wilhelmsen, Fredrik (Fascism, 2022)
While much academic effort has been devoted to exploring various aspects of right-wing extremist lone-actor terrorism, little attention has been devoted to establishing how the terrorists create meaning by locating themselves within a larger narration of history. This article tries to fill this gap, by analysing the conceptions of history and the historical narratives evoked in the manifestos that the right-wing extremist perpetrators uploaded online in relation to the terrorist attacks in Norway on July 22, 2011 and in Christchurch, New Zealand March 15, 2019. Employing a combination of discourse and narrative analysis, the article argues that a shared fascist ‘regime of historicity’ may be identified in the manifestos. Furthermore, it places the narratives found in the manifestos in relation to different right-wing extremist virtual communities.